High Performance Copper Based Metal Organic Framework for Removal of Heavy Metals From Wastewater - Haso, Hussien Waritu; Dubale, Amare Aregahegn; Chimdesa, Mitiku Abdisa; Atlabachew, Minaleshewa (Frontiers in Materials, 2022)
The most challenge of this century is the generation of wastewater which is released to the environment due to the industrial expansion. Industrial development has caused the release of various pollutants including heavy metals such as Cd, Pb and Cr into the environment. In this study, copper diphenylamine metal-organic framework (Cu-DPA MOF) has been synthesized via hydrothermal method and its adsorption capacity towards the removal of heavy metals from wastewater was examined. The removal efficiency of heavy metals by Cu-DPA MOF was tested at optimized adsorption parameters such as optimal adsorbent dosage, pH, initial metals concentration and adsorption time. The heavy metals concentration in the wastewater before treated with the as synthesized MOF was determined to be 0.3027, 0.0098, 0.1021 mg/L for Cr, Cd and Pb respectively. The corresponding concentrations of heavy metals in wastewater were reduced to 0.0015, 0.00024 and 0.00016 mg/L when treated with the as synthesized MOF. As a result a maximum removal efficiency of 97.5 %, 99.5 % and 99.5 % was achieved for Cr, Cd and Pb metals, respectively. This is possibly due to the high porous nature and huge surface area of the as-synthesized MOF. The adsorption data’s were best fitted with Freundlich isotherm throughout this study. The study sheds light on the design of adsorbents with high removal efficiency of pollutants found in the environment.